2012
DOI: 10.1152/jn.00105.2011
|View full text |Cite
|
Sign up to set email alerts
|

Mapping brain activation and information during category-specific visual working memory

Abstract: Linden DE, Oosterhof NN, Klein C, Downing PE. Mapping brain activation and information during category-specific visual working memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 70 publications
6
26
0
1
Order By: Relevance
“…On the other hand, the visual system is also known to be active in delayed reaching and grasping (Singhal et al 2006). Therefore, the activation in this study might also be related to memory of stored representation or visual/kinesthetic imagery (Linden et al 2012).…”
Section: Increased Brain Activation In Patients Compared To Controlsmentioning
confidence: 76%
“…On the other hand, the visual system is also known to be active in delayed reaching and grasping (Singhal et al 2006). Therefore, the activation in this study might also be related to memory of stored representation or visual/kinesthetic imagery (Linden et al 2012).…”
Section: Increased Brain Activation In Patients Compared To Controlsmentioning
confidence: 76%
“…Previous decoding analyses have demonstrated successful decoding of the contents of WM in the absence of delay period activity (Linden et al, 2011; Serences et al, 2009); however, these studies did not rule out the possibility that subpopulations of voxels within their regions of interest may have exhibited delay period activity and contributed disproportionately to their decoding success. One study removed all voxels with significant delay period activity and still observed information about WM items (Riggall & Postle, 2012); however, these results do not preclude the possibility that voxels with greater magnitude delay period activity may contribute more information to a classifier.…”
Section: Discussionmentioning
confidence: 88%
“…These methods have increasingly been applied to the study of how information is represented in WM (Sreenivasan, Curtis, & D'Esposito, in press). Several functional MRI (fMRI) studies utilizing decoding methods have identified patterns of visual activity that code for sensory properties of visual items during WM for those items (Christophel, Hebart, & Haynes, 2012; Ester, Serences, & Awh, 2009; Han, Berg, Oh, Samaras, & Leung, 2013; Harrison & Tong, 2009; Linden, Oosterhof, Klein, & Downing, 2011; Riggall & Postle, 2012; Serences, Ester, Vogel, & Awh, 2009; Xing, Ledgeway, McGraw, & Schluppeck, 2013). Moreover, information about maintained visual items persists in visual cortex throughout the delay period, suggesting that sensory regions participate in the storage of WM information (Harrison & Tong, 2009; Riggall & Postle, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the present results add to the growing body of studies suggesting that load-dependent activity observed in the IPS during VSTM tasks may reflect the operation of mechanisms that are fundamentally attentional in nature, rather than specific to VSTM maintenance (Tsubomi et al, 2013; Magen et al, 2009; Mitchell & Cusack, 2008). Indeed, some have suggested that iIPS delay-period activity during tests of VSTM may not reflect the maintenance of information per se (Emrich et al, 2013; Linden et al, 2012; Riggall & Postle, 2012; but see, Christophel & Haynes, 2014; Christophel et al, 2012) but rather an attentional selection mechanism that is common to tasks that involve the selection and enhancement of a limited number of objects. Other such tasks would include enumeration (Knops et al, 2014) and multiple object tracking (Howe et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, fMRI studies using multi-voxel pattern analysis to decode the contents of VSTM have failed to find activity in the IPS that is associated with the specific contents of VSTM (Emrich, Riggall, Larocque, & Postle, 2013; Linden, Oosterhof, Klein, & Downing, 2012; Riggall & Postle, 2012; but see, Ester, Sprague, & Serences, 2015; Christophel & Haynes, 2014; Christophel, Hebart, & Haynes, 2012). Instead, these studies have observed content-specific activity in regions of sensory visual cortex (e.g., V1, V2, MT+), consistent with the idea that sensory regions may mediate STM processes (e.g., Postle, 2006; Pasternak & Greenlee, 2005).…”
Section: Introductionmentioning
confidence: 99%